الدعوة لغير المسلمين في ماليزيا ومدى انسجامها مع حرية العقيدة في الفكر الإسلامي = Daʿwah to non-muslim in Malaysia and its compatibility with the principle of freedom of belief in Islamic thought - Ahmad, Masitoh; Hashim, Jamil (IIUM Press, 2023)
The article aims at studying and evaluating the methods and approaches used by Da‘wah movements in conveying the message of Islam to non-Muslims in Malaysia, and showing their compatibility with the principle of freedom of belief in Islamic thought. The study used the qualitative methods in which observation and inductive methods are applied while collecting the data related to the methods and approaches used by the Da‘wah movements in the call to non-Muslims. Then, the research analysed the extent of their compatibility with the principle of freedom of belief in Islam. The study concluded that all the Da‘wah organizations have called people to Islam with wisdom and consistence with of the principle of "there is no compulsion in religion". The Da‘wah Movements in Malaysia do not revert people to Islam but offering them their services in various fields without having to pay; Like for instance, giving the medical and health services without any payment due. There is no doubt that the Da‘wah to non-Muslims in Malaysia is keen on caring for human rights in freedom of belief.